EXPERIENCE IN THE EVALUATION OF CHILDREN WITH HEPATOSPLENOMEGALY AT A TEACHING AMBULATORY, SÃO PAULO, BRAZIL - Lucia F. BRICKS; Ana Maria COCOZZA; Rosa RESEGUE; Ana Cecília S.L. SUCUPIRA; Daleth RODRIGUES; Maria Elizabeth B.A. KOBINGER; Maria Lucia M. BOURROUL; Sandra M.C. ZUCCOLOTTO; Ana Maria B. BRESOLIN (Revista do Instituto de Medicina Tropical de São Paulo, 1998)
Objectives: Describe cases of children with hepatosplenomegaly (HS) attended at the General Pediatric Teaching Ambulatory (AGER) of Instituto da Criança, São Paulo, identifying the main causes, evolution, necessity for hospitalization and/or referral to specialists. Methodology: Retrospective analysis of the records of children presenting HS on admission at AGER from September 1, 1993 to August 31, 1996. Results: Of the 89 children included (age range, 1 to 148 months; median, 24 months), 64 (72%) were referred from other services for HS investigation. Most common presenting complaints were: fever - 39 (44%); pallor - 26 (29%); weight loss - 21 (24%) and jaundice - 14 (16%). Main alterations noticed on physical examination were: pallor - 47 (53%) and short stature - 17 (19%). Anemia was diagnosed in 70 children (79%); 35 children (39%) had infections; 7 (8%) metabolic disorders and 5 (6%) neoplastic disorders. The most frequent infections were of the urinary tract - 9 (10%) and hepatitis A - 6 (7%).Thirty six children (40%) were referred to specialists, 17 of which were already diagnosed. Conclusions: Most of the children with HS present deficiency anemia associated with infections which the general pediatrician is able to diagnose. Persistence of unexplained HS for more than 2 months, especially when there is substantial volume enlargement or alteration in the organs consistency, is an indication for referral to specialists. Objetivos: Descrever os casos de crianças com hepatoesplenomegalia (HE) matriculadas no Ambulatório Geral (AGER) do Instituto da Criança, São Paulo, identificando as principais causas, evolução, necessidade de hospitalização e/ou encaminhamento a especialistas. Metodologia: Estudo retrospectivo dos prontuários de crianças matriculadas no AGER para investigação de HE de 01/09/93 a 31/08/96. Resultados: Das 89 crianças incluídas (idade: 1 a 148 meses; mediana, 24 meses), 64 (72%) foram encaminhadas de outros serviços para investigação de HE. As queixas mais freqüentes foram: febre - 39 (44%); palidez - 26 (29%); emagrecimento - 21 (24%) e icterícia - 14 (16%). As principais alterações ao exame físico foram: palidez - 47 (53%) e baixa estatura - 17 (19%). Setenta crianças (79%) apresentavam anemia; 35 (39%) tinham infecções; 7 (8%) doenças metabólicas e 5 (6%) doenças neoplásicas. Trinta e seis crianças (40%) foram encaminhadas a especialistas. Conclusões: A maioria das crianças com HE apresenta anemia carencial associada a infecções que o pediatra geral é capaz de diagnosticar. A persistência de HE inexplicada por mais de 2 meses, especialmente quando existe grande aumento e/ou alteração na consistência dos órgãos é indicação para encaminhar ao especialista.